Sharing of gut microbial strains between selected individual sets of twins cohabitating for decades. - Hyunmin Koo (PLoS ONE, 2019)
BACKGROUND:Given the increasing realization of the important functions of the gut microbial community in human health, it is important to determine whether the increased age of the host coupled with inevitable environmental changes can alter the stability of individual microbial strains of the gut microbial community. Since early studies demonstrated that pairs of twins possess the related gut microbial communities, to gain insights into the temporal stability of the reservoir of gut microbial strains in humans, we have assessed the strain relatedness of samples from two previously published data sets that were obtained from twin children and adults (36-80 years old) who have been either living together or apart for different times. METHODS:We analyzed the two data sets; twin children (n = 24) and adults (n = 50) using our previously developed strain-tracking program called Window-based Single Nucleotide Variant (SNV) Similarity (WSS) that can distinguish a related strain pair from a non-related strain pair based on the overall genome-wide SNV similarity. To independently substantiate the identification of distinct microbial genomic variants (herein strains) observed from WSS analysis, we used analysis by StrainPhlAn. RESULTS:Analysis of the twin children data set revealed a significantly (P-value <0.05) higher number of the shared strain pairs with a predominance of Bacteroides vulgatus between individual sets of twin pairs than the twin adult data set. Additional analysis on the adult twins showed that twins who have been living apart less than 10 years shared significantly more related strain pairs than twins living apart between 10 to 60 years. Eighty-year-old twins who had been living together for 79 years then separated for 1 year showed the highest number of related strain pairs consisting of B. vulgatus, Eubacterium eligens, and Bifidobacterium adolescentis. The next highest number of related strain pairs was found in 56-year-old twins who had been living together for 51 years then separated for 5 years (B. vulgatus and Coprococcus eutactus as related strains), 73-year-old twins living together for 66 years and then separated for 7 years (Bacteroides uniformis and Clostrium sp. L2-50 as related strains) and 36-year-old twins separated for 19 years (shared strains of Alistipes shahii and E. eligens). Finally, a sporadic appearance of a single shared strain that did not show a correlation with time of separation was observed in three twin sets that had separation times between 22 to 54 years. CONCLUSION:We conclude from our strain-tracking analysis of twins that certain gut microbial strains can be shared between individuals in some cases for decades. Changes in the host environmental conditions over time can impact the stability landscape of the gut microbial community resulting in the appearance of new strains that could potentially impact microbe interactions that are essential for function in human health.